The performance and reaction pathway of δ-MnO2/USY for catalytic oxidation of toluene in the presence of ozone at room temperature. (May 2020) - Yang, Ruijie; Han, Pingping; Fan, Yingying; Guo, Zhongjie; Zhao, Qitong; Wang, Yang; Che, Sainan; Lin, Songxue; Zhu, Rongshu
Abstract: In this work, a series of δ-MnO2 /USY with different contents of δ-MnO2 (0.3 wt%, 1.5 wt%, 3.0 wt%, 10.0 wt%, and 15.0 wt%) were prepared. In addition, their performances of the adsorption of toluene, degradation and mineralization of toluene, and removal of ozone (O3 ) were investigated. The results showed that, among all the samples, 3.0 wt% δ-MnO2 /USY displayed the best performance of toluene adsorption, degradation and mineralization. Furthermore, according to the in situ DRIFTS and GC-MS analysis, the intermediate by-products during the toluene degradation progress were ascertained and the possible pathway of catalytic oxidation toluene by δ-MnO2 /USY in the presence of O3 was proposed. Graphical abstract: A series of δ-MnO2 /USY with different contents of δ-MnO2 (0.3 wt%, 1.5 wt%, 3.0 wt%, 10.0 wt%, and 15.0 wt%) were prepared successfully using hydrothermal method. Among all the samples, 3.0 wt% δ-MnO2 /USY shows the strongest capacity for toluene adsorption, degradation and mineralization. According to the chemical bond energy, the possible pathway of catalytic oxidation toluene by δ-MnO2 /USY in the presence of O3 was proposed. Image 1087 Highlights: A series of δ-MnO2 /USY with different contents of δ-MnO2 were prepared successfully. 3.0 wt% δ-MnO2 /USY shows the strongest capacity for toluene degradation. The major by-product generation pathway is: C6 H5 –CH3 .→C6 H5 CH2 –OH→C6 H5 CHO→C6 H5 COOH.